Meanings, Preferences, and Power among Men Having Sex with Men in Manila - Acaba, Jeffry P. (Philippine Social Sciences Review; Vol. 65 No. 2 July-Dec 2013, Ed. Rolando Esteban, 2014)
This study explores the meanings, preferences, and power relations ascribed to sexual roles. One hundred and seventy-eight men having sex with men (MSM) participated in an online survey in 2010, seven of whom participated in a face-to-face in-depth interview in order describe the scripts attached to sexual roles, preferences for sexual partners, and perceptions of HIV risks. Sexual identities do not dictate sexual roles, which depends on choice based on experience, negotiation, emotional attachment, and power relations. No significant difference was found between sexual roles and physical traits, which suggest that physical characteristics are not a gauge in looking for a potential sexual partner. Power dynamics between men also implicate reciprocity. There is a need to integrated masculinity, power dynamics, and sex in HIV education programs toward the demystification of misconceptions about sex roles and risks to HIV.
Keywords: men having sex with men, sexual identity, sexual role, sexual preference, masculinity, heteronormativity